SAT0389 FREQUENCY OF DISEASE FLARES UNDER LONG-TERM ANTI-TNF THERAPY IN PATIENTS WITH EARLY AXIAL SPONDYLOARTHRITIS: RESULTS FROM THE ETANERCEPT VERSUS SULFASALAZINE IN EARLY AXIAL SPONDYLOARTHRITIS TRIAL. (2nd June 2020) - Proft, F.; Torgutalp, M.; Weiß, A.; Protopopov, M.; Rios Rodriguez, V.; Haibel, H.; Hermann, K.; Althoff, C.; Behmer, O.; Sieper, J.; Poddubnyy, D.
Abstract : Background: Disease flares in axial spondyloarthritis (axSpA) might occur even in patients with otherwise stable disease receiving highly effective anti-inflammatory therapy such as TNF inhibitors. The frequency of disease flares, especially in patients with axSpA receiving long-term stable therapy, and factors associated with flares are not sufficiently investigated. Objectives: The objective was to assess the frequency of disease flares and to identify factors associated with flares in patients with early axSpA receiving continuous long-tem (up to 10 years) treatment with a TNF inhibitor etanercept. Methods: In the ESTHER (etanercept versus sulfasalazine in early axial spondyloarthritis trial), patients with early axSpA (symptom duration ≤5 years) were treated with ETN (n=40) versus sulfasalazine (n=36) for 48 weeks [2]. After one year all patients were treated continuously with etanercept (n=17 patients temporarily interrupted treatment in the 2nd year to assess time to flare and were then (re-)treated with etanercept, except 4 patients who completed the study in sustained remission) for up to 10 years in total. Only patients who were continuously treated with etanercept for at least 6 months were included in the current analysis. The disease flare was defined as a worsening of the ASDAS by ≥0.9 as compared to the value obtained at the previous visit. Univariate and multivariable cox-regression analyses were performed to analyze the predictors of flares. Results: Out of 76 patients who entered the study at baseline, 62 patients (n=32 with radiographic (r-) axSpA and n=30 with non-radiographic (nr-) axSpA) fulfilled the criterion of the continuous etanercept treatment. A total of 22 patients (35%) experienced at least one flare over the entire treatment period 10 patients (31.3%) in the r-axSpA and 12 patients (40%) in the nr-axSpA subgroup) - figure. A total of 81 flares occurred (33 and 48 in the r- and nr-axSpA subgroups, respectively) in the 10 years of follow-up. None of the documented disease flares resulted in a direct study withdrawal. The majority of flares occurred within first 4 years of treatment (figure). There were also no statistically significant differences between nr- and r-axSpA in the time until the first flare (p=0.4, Log-rank test). In the multivariable Cox regression analysis normal CRP values (≤5mg/l), HLA-B27 negativity, higher physician global assessment, a longer symptom duration at study entry, higher spinal ankylosis and higher fatty degeneration in the sacroiliac joints but lower spinal osteitis scores and lower ankylosis scores in the sacroiliac joints at baseline MRI were associated with a higher risk for flares. Conclusion: Disease flares according to the ASAS definition of clinically important worsening in axSpA based on ASDAS occurred 1/3 of patients with early axSpA who received a treatment with etanercept for up to 10 years without major differences between r- and nr- forms of axSpA. HLA-B27 negativity, normal CRP, higher spinal ankylosis scores, higher fatty degeneration scores but lower ankylosis scores in the SIJ´s at baseline MRI were associated with a higher risk for flares. Acknowledgments: The ESTHER study was supported by an unrestricted research grant from Pfizer. Murat Torgutalp's (MT) work at Charité - Universitätsmedizin was supported by an award from the Scientific and Technological Research Council of Turkey (TUBITAK). Disclosure of Interests: Fabian Proft Grant/research support from: Novartis Pharma GmbH, Consultant of: Consultancy / speaker fees from: Abbvie, BMS, Celgene, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: Consultancy / speaker fees from: Abbvie, BMS, Celgene, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Murat Torgutalp: None declared, Anja Weiß: None declared, Mikhail Protopopov Consultant of: Novartis, Valeria Rios Rodriguez Consultant of: Abbvie, Novartis, Hildrun Haibel Consultant of: Abbvie, Jansen, MSD, and Novartis, Speakers bureau: Abbvie, Jansen, MSD, and Novartis, Kay Hermann: None declared, Christian Althoff: None declared, Olaf Behmer Employee of: Pfizer Pharma GmbH, Joachim Sieper Consultant of: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Speakers bureau: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB